Sun Florist: beautiful flowers and styling / Siti Hajar Sudin... [et al.] - Sudin, Siti Hajar; Yaakob, Syarah 'Afifah; Mohd Othman, Nur Liyana; Kamaludin, Nur Shahirah; Mohd Aluwi, Noralajnani (2015)
Sun Florist is a business that fully owned by Malaysia citizen. Sun Florist are operated by five partnership. The target market that we want to focus is adult who is a women around Kulim, Kedah. The nature of business is product. Our product of course is the flower.